The Company You Keep: How Voters Infer Party Positions on European Integration from Governing Coalition Arrangements. Issue 4 (25th November 2015) - Adams, James; Ezrow, Lawrence; Wlezien, Christopher
Abstract: Recent studies document that voters infer parties' left‐right positions from governing coalition arrangements. We show that citizens extend this coalition‐based heuristic to the European integration dimension and, furthermore, that citizens' coalition‐based inferences on this issue conflict with alternative measures of party positions derived from election manifestos and expert placements. We also show that citizens' perceptions of party positions on Europe matter, in that they drive substantial partisan sorting in the electorate. Our findings have implications for parties' election strategies and for mass‐elite policy linkages .